Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1177/002215549804601204
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Carboxypeptidases E and D in the Human Placenta and Umbilical Cord

Abstract: SUMMARY Carboxypeptidase E (CPE) is highly concentrated in neuroendocrine tissues and is the only carboxypeptidase detected in mature secretory vesicles. Carboxypeptidase D (CPD), a carboxypeptidase with CPE-like activity, is widely distributed in tissues and is present in the trans-Golgi network. Previous work had shown that both CPE and CPD are expressed in the human placenta and that CPD is expressed at much higher levels than CPE. The present work provides evidence for the co-localization of CPE and CPD to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…We have demonstrated that pro-IGF-II is processed at two separate sites: RLRR 104 2 and KSER 68 2 to generate IGF-II (1-104) and IGF-II (1-68), respectively. Exposed basic residues at the carboxyl terminal are further cleaved by carboxypeptidases E and D (26), which are widely distributed in the placenta (27). Therefore, Arg-68 is further cleaved from IGF-II (1-68) to generate a peptide containing 67 amino acids, the mature IGF-II (1-67) form.…”
Section: Discussionmentioning
confidence: 99%
“…We have demonstrated that pro-IGF-II is processed at two separate sites: RLRR 104 2 and KSER 68 2 to generate IGF-II (1-104) and IGF-II (1-68), respectively. Exposed basic residues at the carboxyl terminal are further cleaved by carboxypeptidases E and D (26), which are widely distributed in the placenta (27). Therefore, Arg-68 is further cleaved from IGF-II (1-68) to generate a peptide containing 67 amino acids, the mature IGF-II (1-67) form.…”
Section: Discussionmentioning
confidence: 99%
“…Several carboxypeptidases have been described in vascular SMC, where they function to either activate or inactivate proteins involved with vasomotion or growth (32)(33)(34)). An aortic carboxypeptidase-like protein was shown to be up-regulated during vascular SMC differentiation in vitro (35).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular distribution of carboxypeptidase Z is restricted to specific cell types, such as the leptomeningeal cells in brain (36). In contrast, CPD has a broad tissue distribution and is present in many cell types in each tissue (37)(38)(39)(40). Also, CPD is present along with furin in the trans Golgi network and immature secretory vesicles (41,42).…”
mentioning
confidence: 99%